The wind‐driven formation of cross‐shelf sediment plumes in a large lake. (4th February 2019) - McKinney, Paul; Austin, Jay; Fai, Gills
Abstract: Wind‐driven turbidity plumes frequently occur in the western arm of Lake Superior and may represent a significant cross‐shelf transport mechanism for sediment, nutrient, and biota. Here, we characterize a plume that formed in late April 2016 using observations from in situ sensors and remote sensing imagery, and estimate the volume of cross‐shelf transport using both the observations and an idealized analytical model of plume formation. The steady‐state, barotropic model is used to determine a relationship between the intensity and duration of a wind event and the volume of water transported from nearshore to offshore during the event. The model transport is the result of nearshore flow in the direction of the wind and a pressure‐gradient‐driven counter flow in the deeper offshore waters, consistent with observations. The volume of offshore transport associated with the 2016 plume is estimated by both methods to have been on the order of 10 10  m 3 . Analysis of similar events from 2008 to 2016 shows a strong relationship between specific wind impulse and plume volume. Differences in the intensity and duration of individual events as well as ice cover, which prevents plume formation, lead to interannual variability of offshore transport ranging over an order of magnitude and illustrates how wind‐driven processes may contribute to interannual variability of ecosystem functioning.